“Is Judah indeed the Teutonic Fatherland?”: The Debate over the Hebrew Legacy at the Turn of the 18th Century - Ilani, ʿOfri (Naharaim, 2014)
The article presents the eighteenth-century discussion on the place of Hebrew legacy within German culture. It argues that the exemplar of Hebrew poetry played a pivotal role in the work of a group of influential writers, especially members of the Sturm und Drang movement. As a reaction to anti-Biblical attacks by Deists and radical Enlightenment philosophers, German thinkers and poets posited the Old Testament as a model for sentimental and patriotic poetry. The Hebrew model acted as one of the cultural elements that allowed German literature of that period to distinguish itself from French-identified Neoclassical literature and develop its own stylistic and thematic avenues. In the first decades of the nineteenth century, new myths such as the Hindu-Aryan myth dethroned Hebrew myth from its central role in German identity. However, the search for the roots of German culture in Asia grew out of biblical scholarship, and only gradually disengaged from it.